2009
DOI: 10.1242/jcs.035287
|View full text |Cite
|
Sign up to set email alerts
|

Role of cleavage by separase of the Rec8 kleisin subunit of cohesin during mammalian meiosis I

Abstract: SummaryRole of cleavage by separase of the Rec8 kleisin subunit of cohesin during mammalian meiosis I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 51 publications
5
98
0
4
Order By: Relevance
“…Although abnormal spermatids with a 4C DNA content are known to be generated by the inhibition of caspaseinduced Rec8 cleavage (Kudo et al, 2009), incomplete release of cohesin in TH2A/TH2B-deficient spermatocytes did not result in the accumulation of abnormal spermatids with a 4C DNA content. Recently, Montellier et al (2013) reported that mutant mice lacking TH2B expression exhibit no defect during spermiogenesis, indicating that a loss of TH2B alone is not sufficient to disturb histone replacement.…”
Section: Introductionmentioning
confidence: 85%
“…Although abnormal spermatids with a 4C DNA content are known to be generated by the inhibition of caspaseinduced Rec8 cleavage (Kudo et al, 2009), incomplete release of cohesin in TH2A/TH2B-deficient spermatocytes did not result in the accumulation of abnormal spermatids with a 4C DNA content. Recently, Montellier et al (2013) reported that mutant mice lacking TH2B expression exhibit no defect during spermiogenesis, indicating that a loss of TH2B alone is not sufficient to disturb histone replacement.…”
Section: Introductionmentioning
confidence: 85%
“…The first involves negative phosphorylation by Cdk1 and the second involves binding to a chaperone protein called securin (initially called PTTG in human cells) (Shindo et al, 2012). During exit from both MI and at fertilization in MII, separase needs to be activated (Kudo et al, 2006;Kudo et al, 2009). This is triggered directly by a loss of securin and indirectly via a loss of cyclin B1, both of which are effected by the anaphasepromoting complex/cyclosome (APC), as discussed below.…”
Section: The Roles Of Cdk1 and Separase In Meiosismentioning
confidence: 99%
“…22,24,25 In addition to the regulation of gene expression, cohesin has also other important functions: it forms a huge tripartite ring, mediates the sister chromatid cohesion, and facilitates the repair of damaged DNA. 26,27 From our analysis, we can postulate that HLA-DQA1 and HLA-DRB1 may represent a genetic biomarker for predicting differences in ID conditions, but also that polymorphisms or mutations of the cohesin subunits might have an important role for the non-disjunction of the chromosomes 21 and/or for the dysregulation of the expression of many genes.…”
Section: Gene Expression and Iq In Trisomy 21mentioning
confidence: 92%